1988
DOI: 10.1111/j.1365-2559.1988.tb02000.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary lymphoma: a re‐appraisal of its histogenesis and its relationship to pseudolymphoma and lymphoid interstitial pneumonia

Abstract: The clinical, morphological and immunohistochemical features of 15 cases of pulmonary lymphoproliferative disease are described. The diagnosis of primary pulmonary lymphoma was based in 13 cases on the demonstration of light chain restriction and in two cases on morphological characteristics. Many patients had a prolonged clinical course without significant clinical or radiographic deterioration, a feature associated with malignant lymphomas of mucosa-associated lymphoid tissue in other sites. Lymphoepithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
95
0
4

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(101 citation statements)
references
References 26 publications
(18 reference statements)
2
95
0
4
Order By: Relevance
“…If the consolidation appears diffuse, a feature which has previously been called LIP (Fig. 3), it is likely to reflect parenchymal extension of MALT lymphoma from peribronchial/peribronchiolar regions [6]. There appears to be no lobar predilection and air bronchograms are a well recognized feature, particularly on CT, irrespective of pattern or distribution of tumour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the consolidation appears diffuse, a feature which has previously been called LIP (Fig. 3), it is likely to reflect parenchymal extension of MALT lymphoma from peribronchial/peribronchiolar regions [6]. There appears to be no lobar predilection and air bronchograms are a well recognized feature, particularly on CT, irrespective of pattern or distribution of tumour.…”
Section: Discussionmentioning
confidence: 99%
“…He did, however, warn that histological differentiation between a malignant lymphoma and pseudolymphoma was not always possible. Since then, the introduction of immunohistochemical and molecular genetic methods has confirmed that most of these tumours are, in fact, low-grade monoclonal B-cell lymphomas [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical staining is essential for certain diagnosis. Especially when the biopsy specimen is small, alternatives such as diffuse lymphoid hyperplasia, interstitial lymphoid pneumonia, and follicular bronchitis must be considered (15). Bone marrow involvement is mostly seen with nodal or splenic MZL.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also concluded that the majority of neoplasms with a low-grade cytological appearance should be considered as reactive proliferations, introducing the term ''pseudolymphoma''. This hypothesis showed significant weak points and, approximately 20 years later, ADDIS et al [3] concluded that ''most if not all the cases of pseudo-lymphoma can be classified, when re-evaluated, as malignant lymphoma''. Knowledge of these entities expanded rapidly after the advent of new investigative tools such as immunohistochemistry and molecular biology techniques.…”
mentioning
confidence: 99%